TRANSVERSAL ANALYSIS OF THE FREQUENCY OF LORDOTIC DEFORMITIES IN THE THE TELVE-YEAR OLD BOYS AND GIRLS - Veselin Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
of lordotic spinal deformities were determined. The sample was drawn from the population of pupils of fi fth grade from the primary school «L. Simonović» in Nikšić. The state and the structure of lordotic deformities were determined by use of combined measuring methods and techniques, applicable to the mass research in schools. The research proved that lordotic deformities are represented by a considerable percentage in the given population. The highest percentage of the deformities are mild, functional disruptions which can be successfully removed by an appropriate corrective treatment. Our sample proved that lordotic deformities appear most frequently in the lumbal area of the spinal chord.